Assessment of health-related quality of life of COVID-19 patients during follow-up - Khan, Abed Hussain; Arafat, Shohael Mahmud; Alam, Md Adnanul; Sharmin, Elora (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: The COVID-19 pandemic has had a significant impact on the quality of life of individuals worldwide. The aim of this study was to assess the health-related quality of life (HRQOL) and its associated factors among COVID-19 patients discharged from hospital. Methods: This facility-based cross-sectional study was conducted among laboratory confirmed COVID-19 patients who were discharged from medicine department of Bangabandhu Sheikh Mujib Medical University and did their first-month follow-up from April to September 2021. A validated Bengali version of International Quality of Life Assessment, Short form – 36 (SF-36) questionnaire was used to assess the HRQOL status. Univariate and multivariate analyses were done for identifying factors associated with low HRQOL. Result: Out of 225 patients, the mean (standard deviation) age was 36.9 (14.2) years and four in every ten patients were women. Out of eight subgroups, almost all scored averagely 79 out of 100. Older age, rural residence and severe to critical disease was reported as factors for low physical and mental component summary of SF-36. Conclusion: COVID-19 patients with older age, rural residence and having severe to critical disease condition need to be addressed critically as they have a higher chance of having low HRQOL status after COVID-19 infection.